예비 교사의 TPACK 향상을 위한 프로그래밍 기반 TPACK 교육 프로그램 적용 - 김성원(Seong-Won Kim) (한국컴퓨터정보학회논문지, 2020)
본 연구에서는 설계 기반 연구를 통한 프로그래밍 기반 TPACK 교육 프로그램의 개선이 예비교사에 TPACK에 미치는 효과를 검증하였다. 연구 대상은 K 대학에 다니고 있는 예비 교사이며, 강의를 통하여 통제 집단 129명과 실험 집단 126명을 모집하였다. 처치는 설계 기반 연구에서 개발한 교육 프로그램을 사용하였다. 검사 도구는 박기철과 강성주(2014)에서 개발한 TPACK 검사도구를 사용하였다. 검사 결과는 독립 표본 t-검정과 대응 표본 t-검증을 통해 분석하였다. 연구결과, 1차 교육 프로그램은 TPK와 TPACK 향상에만 효과적이었지만, 프로그램 개선을 통하여PCK, TCK, TK(2차), PK(3차), CK(최종)의 향상에도 효과적인 교육 프로그램을 개발하였다. 따라서설계 기반 연구를 통하여 예비 교사의 TPACK 향상에 효과적인 프로그래밍 기반 TPACK 교육 프로그램을 개발한 것을 확인할 수 있었다. This study verified the effects that a programming-based TPACK education program, through design-based research on TPACK, had on pre-service teachers. The research subjects were pre-service teachers attending teacher training at a university in Korea, and 129 control groups and 126 experimental groups were recruited through lectures. The treatment used a TPACK educational program developed in a design-based study (Kim & Lee, 2019). A TPACK test tool developed by Park and Kang (2014) was used. The test results were analyzed via independent sample t-test and paired sample t-test. The results show that the programming-based TPACK education program (first cycle) was only effective in improving TPK and TPACK, but an effective educational program was developed to improve PCK, TCK, TK (second cycle), PK (third cycle), and CK (final cycle). This design-based research therefore confirmed the development of a programming-based TPACK education program that was effective for improving the TPACK of pre-service teachers. KCI Citation Count: 0